Important Resources for the Development and Sustainability of School Garden Programs - John M. Diaz; Erin Elsberry (EDIS, 2017)
This 3-page document provides an outline of important resources to help in the development and sustainability of a school garden program. Resource categories include Extension support, garden planning, curricula, and funding. Written by John M. Diaz and Erin Elsberry, and published by the Agricultural Education and Communication Department, May 2017.